A novel energy management strategy for LNG ambient air vaporizer coupled with water-bath heater system - Lemei Ren; Wenling Jiao; Guansan Tian (Case Studies in Thermal Engineering)
Water-bath heater (WH) is typically installed in series behind ambient air vaporizers (AAVs) to heat liquefied natural gas (LNG) to a desired temperature, while accounting for the uncertainty in the heat transfer performance of AAV. This paper proposes a novel energy management strategy for an LNG AAV coupled with WH system to reduce the energy consumption of the WH. The strategy incorporates a heat transfer model for the AAV and a compensator model for the WH to determine the hot water supply temperature. By utilizing these models, the heat transfer capacity of the WH can be adjusted based on the variations in the AAV's heat transfer performance and the flow rate of the exported natural gas (NG). Operational data from LNG gasification stations were employed to validate these models. Additionally, an example was provided to compare the novel and traditional strategies. The energy consumption was reduced by 40 %, and the temperature fluctuations of the exported NG were maintained within a narrow range, not exceeding 1 °C. These findings indicate that the novel energy management strategy significantly improves the efficiency of LNG gasification and decreases energy consumption.